1995
DOI: 10.2307/3440530
|View full text |Cite
|
Sign up to set email alerts
|

Theories of Pay and Unemployment: Survey Evidence from Swedish Manufacturing Firms

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0
6

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(157 citation statements)
references
References 14 publications
9
142
0
6
Order By: Relevance
“…6 In Benabou (2000), on the other hand, multiplicity originates in imperfect credit and insurance markets. When inequality is low, there is strong political support for redistribution as a way to correct for capital-market imperfections, which in turn results to high efficiency and low inequality; when instead inequality 5 Actually, experimental studies and the evidence on charitable donations suggest that Americans are perhaps more altruistic that Europeans, which alone would predict more rather than less redistribution in the United States.…”
Section: Fairness and Redistributionmentioning
confidence: 99%
“…6 In Benabou (2000), on the other hand, multiplicity originates in imperfect credit and insurance markets. When inequality is low, there is strong political support for redistribution as a way to correct for capital-market imperfections, which in turn results to high efficiency and low inequality; when instead inequality 5 Actually, experimental studies and the evidence on charitable donations suggest that Americans are perhaps more altruistic that Europeans, which alone would predict more rather than less redistribution in the United States.…”
Section: Fairness and Redistributionmentioning
confidence: 99%
“…Campbell and Kamlani (1997) (Table II) report results from other studies based on survey data from firms which suggest that relative wage concern is very significant, especially in heavily unionized firms (Agell and Lundborg (1995)). …”
Section: Some Empirical Evidencementioning
confidence: 77%
“…For instance, Acemoglu [1] shows, with US data, that the sorting of workers across occupations increased between 1983 and 1993. 2 Davis and Haltinwanger [17] had already observed that the rise of wage inequality in America is imputable in part to differently abled workers sorting themselves across firms: "The tremendous magnitude of the rise in the size-wage gap indicates that sorting by worker ability across plants of different sizes probably increased over time (pp. 156-157)."…”
Section: Literature On Labor Market Segregationmentioning
confidence: 99%
“…The less productive, on the other hand, are paid more than their marginal productivity to compensate for their "suffering" caused by an inferior wage. 15 Fershtman et al [22], in a similar framework, explore the effects of status on effort, and show that firms with 6 Other papers which offer survey evidence on the importance of equity concerns in organizations are: Blinder and Choi [8], Bewley [6], Agell and Lundborg [2,3], or Campbell and Kamlani [15]. 7 Bewley [7, Table 6.5].…”
Section: Literature On Economic Implications Of Social Preferencesmentioning
confidence: 99%